Sei sulla pagina 1di 4

Solve x^(2)+2x-12=0 Tiger Algebra Solver

http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/

Solver http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/ 27,547,935 solved | 434 online Algebra Calculator | Latest
Solver http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/ 27,547,935 solved | 434 online Algebra Calculator | Latest

27,547,935 solved | 434 online

Algebra Calculator | Latest | Discuss | About | Help | Translation

x^(2)+2x-12=0

| Discuss | About | Help | Translation x^(2)+2x-12=0 x ( 2 ) +2x-12=0 Two solutions

x (2) +2x-12=0

Two solutions were found :

1. x =(-2-52)/2=-1-13 = -4.606

2. x =(-2+52)/2=-1+13 = 2.606

Step by step solution :

Step

1

:

Trying to factor by splitting the middle term

1.1 Factoring x 2 +2x-12

The first term is, x 2 its coefficient is 1 . The middle term is, +2x its coefficient is 2 . The last term, "the constant", is -12

Step-1 : Multiply the coefficient of the first term by the constant

1 -12 = -12

Latest drills solved

y=-2xterm by the constant 1 • -12 = -12 Latest drills solved 7x-8y=-23 (8x^3)+125 h-16<-24 k^4-16

7x-8y=-23

(8x^3)+1251 • -12 = -12 Latest drills solved y=-2x 7x-8y=-23 h-16<-24 k^4-16 3(t-4)-8(2-3t) lcm3,8,12 x(x-8)=0

h-16<-24-12 = -12 Latest drills solved y=-2x 7x-8y=-23 (8x^3)+125 k^4-16 3(t-4)-8(2-3t) lcm3,8,12 x(x-8)=0 6x^2+x^3-2

k^4-16Latest drills solved y=-2x 7x-8y=-23 (8x^3)+125 h-16<-24 3(t-4)-8(2-3t) lcm3,8,12 x(x-8)=0 6x^2+x^3-2 findlcmof6,2,12

3(t-4)-8(2-3t)drills solved y=-2x 7x-8y=-23 (8x^3)+125 h-16<-24 k^4-16 lcm3,8,12 x(x-8)=0 6x^2+x^3-2 findlcmof6,2,12

lcm3,8,127x-8y=-23 (8x^3)+125 h-16<-24 k^4-16 3(t-4)-8(2-3t) x(x-8)=0 6x^2+x^3-2 findlcmof6,2,12 3x^3y-9x^2y^2-30xy^2

x(x-8)=0(8x^3)+125 h-16<-24 k^4-16 3(t-4)-8(2-3t) lcm3,8,12 6x^2+x^3-2 findlcmof6,2,12 3x^3y-9x^2y^2-30xy^2

6x^2+x^3-2h-16<-24 k^4-16 3(t-4)-8(2-3t) lcm3,8,12 x(x-8)=0 findlcmof6,2,12 3x^3y-9x^2y^2-30xy^2 0.0284x^2+0.0388x-1=0

findlcmof6,2,12k^4-16 3(t-4)-8(2-3t) lcm3,8,12 x(x-8)=0 6x^2+x^3-2 3x^3y-9x^2y^2-30xy^2 0.0284x^2+0.0388x-1=0

3x^3y-9x^2y^2-30xy^2

0.0284x^2+0.0388x-1=0

((z+9)(z+3))/((z+9)(z+4))

1215=5*(9p)^5/40.0284x^2+0.0388x-1=0 ((z+9)(z+3))/((z+9)(z+4)) 8x^3 − 64=0 Step-2 : Find two factors of -12 whose sum

((z+9)(z+3))/((z+9)(z+4)) 1215=5*(9p)^5/4 8x^3 − 64=0 Step-2 : Find two factors of -12 whose sum

8x^364=0

Step-2 : Find two factors of -12 whose sum equals the coefficient of the middle term,

which is

2 .

Subscribe to our mailing list

Email Address

-12

+

1

=

-11

 

-6

+

2

=

-4

-4

+

3

=

-1

-3

+

4

=

1

-2

+

6

=

4

Translate

-1

+

12

=

11

+ 6 = 4 Translate -1 + 12 = 11 Observation : No two such factors

Observation : No two such factors can be found !! Conclusion : Trinomial can not be factored

Equation at the end of step 1 :

x 2 + 2x - 12

= 0

Step

2

:

Parabola, Finding the Vertex :

2.1 Find the Vertex of

y = x 2 +2x-12

Parabolas have a highest or a lowest point called the Vertex . and accordingly has a lowest point (AKA absolute minimum) .

before plotting "y" because the coefficient of the first term, 1 , is positive (greater

than zero).

Our parabola opens up We know this even

English(greater than zero). Our parabola opens up We know this even Spanish Russian Portuguese Indonesian Vietnamese

Spanishthan zero). Our parabola opens up We know this even English Russian Portuguese Indonesian Vietnamese Chinese

RussianOur parabola opens up We know this even English Spanish Portuguese Indonesian Vietnamese Chinese Polish German

Portugueseparabola opens up We know this even English Spanish Russian Indonesian Vietnamese Chinese Polish German French

Indonesianup We know this even English Spanish Russian Portuguese Vietnamese Chinese Polish German French Italian Dutch

Vietnameseknow this even English Spanish Russian Portuguese Indonesian Chinese Polish German French Italian Dutch Czech Turkish

Chinese

PolishSpanish Russian Portuguese Indonesian Vietnamese Chinese German French Italian Dutch Czech Turkish 1 of 4 8/Oct-17,

GermanRussian Portuguese Indonesian Vietnamese Chinese Polish French Italian Dutch Czech Turkish 1 of 4 8/Oct-17, 11:26

Russian Portuguese Indonesian Vietnamese Chinese Polish German French Italian Dutch Czech Turkish 1 of 4 8/Oct-17,

Russian Portuguese Indonesian Vietnamese Chinese Polish German French Italian Dutch Czech Turkish 1 of 4 8/Oct-17,

French

ItalianSpanish Russian Portuguese Indonesian Vietnamese Chinese Polish German French Dutch Czech Turkish 1 of 4 8/Oct-17,

DutchRussian Portuguese Indonesian Vietnamese Chinese Polish German French Italian Czech Turkish 1 of 4 8/Oct-17, 11:26

CzechRussian Portuguese Indonesian Vietnamese Chinese Polish German French Italian Dutch Turkish 1 of 4 8/Oct-17, 11:26

TurkishSpanish Russian Portuguese Indonesian Vietnamese Chinese Polish German French Italian Dutch Czech 1 of 4 8/Oct-17,

Solve x^(2)+2x-12=0 Tiger Algebra Solver

http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/

Top | privacy policy | terms of service | Copyright ©2013-2017 tiger-algebra.com 7berge Gmbh

Find us on Google+ html css built with

Each parabola has a vertical line of symmetry that passes through its vertex. Because

of

this symmetry, the line of symmetry would, for example, pass through the midpoint

of

the two x -intercepts (roots or solutions) of the parabola. That is, if the parabola has

indeed two real solutions.

Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.

For any parabola,Ax 2 +Bx+C,the x -coordinate of the vertex is given by -B/(2A) . In our case the x coordinate is -1.0000

Plugging into the parabola formula -1.0000 for x we can calculate the

y -coordinate :

y = 1.0 * -1.00 * -1.00 + 2.0 * -1.00 - 12.0

or

y = -13.000

Parabola, Graphing Vertex and X-Intercepts :

Root plot for : y = x 2 +2x-12 Axis of Symmetry (dashed) {x}={-1.00} Vertex at {x,y} = {-1.00,-13.00}

x -Intercepts (Roots) :

Root 1 at {x,y} = {-4.61, 0.00} Root 2 at {x,y} = { 2.61, 0.00}

1 at {x,y} = {-4.61, 0.00} Root 2 at {x,y} = { 2.61, 0.00} Terms and

Terms and Topics

Simplifying Radicals

Solving Quadratic Equations by Completing The Square

Solving Quadratic Equations using the Formula

Parabola Finding Vertex and X Intercepts

Related Links

Quadratic Equations

Solving Quadratic Equations by Completing the Square | Purplemath

Solving Quadratic Equations with the Quadratic Formula | Purplemath

Solving Equations Algebraically

transitive law | logic and mathematics | Britannica.com

http://www.uiowa.edu/~examserv/mathmatters

/tutorial_quiz/geometry

/findingvertexofparabola.html

Axis of Symmetry and Vertex, Parabola, Graphing, Maths Year 9, NSW | Online Education Home Schooling Skwirk Australia

Parabolas

SOLVING EQUATIONS

http://www.regentsprep.org/Regents/math/algtrig

/ATO3/simpradlesson.htm

Solve Quadratic Equation by Completing The Square

2.2 Solving

x 2 +2x-12 = 0 by Completing The Square .

Add 12 to both side of the equation :

x 2 +2x = 12

Now the clever bit: Take the coefficient of x , which is 2 , divide by two, giving 1 , and finally square it giving 1

Add 1 to both sides of the equation :

On the right hand side we have :

12 + 1 or, (12/1)+(1/1) The common denominator of the two fractions is 1 So adding to both sides we finally get :

x 2 +2x+1 = 13

Adding (12/1)+(1/1) gives 13/1

Adding 1 has completed the left hand side into a perfect square :

x 2 +2x+1 = (x+1) • (x+1) = (x+1) 2 Things which are equal to the same thing are also equal to one another. Since x 2 +2x+1 = 13 and

Solve x^(2)+2x-12=0 Tiger Algebra Solver

x 2 +2x+1 = (x+1) 2 then, according to the law of transitivity, (x+1) 2 = 13

We'll refer to this Equation as Eq. #2.2.1

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of (x+1) 2 is (x+1) 2/2 = (x+1) 1 =

x+1

Now, applying the Square Root Principle to Eq. #2.2.1 we get:

x+1 = 13

Subtract 1 from both sides to obtain:

x = -1 + 13

Since a square root has two values, one positive and the other negative x 2 + 2x - 12 = 0 has two solutions:

x = -1 + 13

or

x = -1 - 13

Solve Quadratic Equation using the Quadratic Formula

2.3 Solving

x 2 +2x-12 = 0 by the Quadratic Formula .

According to the Quadratic Formula, x , the solution for

and C are numbers, often called coefficients, is given by :

Ax 2 +Bx+C = 0 , where A, B

x =

- B

± B 2 -4AC

————————

2A

In

our case, A

=

C =

B

=

2

-12

1

Accordingly, B 2 - 4AC 4 - (-48) =

52

=

Applying the quadratic formula :

x

=

-2 ± 52 —————

2

Can 52 be simplified ?

Yes!

The prime factorization of 52

2•2•13

is

To be able to remove something from under the radical, there have to be 2 instances of it (because we are taking a square i.e. second root).

52 = 2•2•13 =

±

2 13

13 , rounded to 4 decimal digits, is 3.6056 So now we are looking at:

x

=

( -2 ± 2 •

3.606 ) / 2

http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/

Solve x^(2)+2x-12=0 Tiger Algebra Solver

Two real solutions:

x =(-2+52)/2=-1+13 = 2.606

or:

x =(-2-52)/2=-1-13 = -4.606

Two solutions were found :

1. x =(-2-52)/2=-1-13 = -4.606

2. x =(-2+52)/2=-1+13 = 2.606

Processing ends successfully

http://www.tiger-algebra.com/drill/x~(2)_2x-12=0/